Temporal distribution of the transferrin alleles (Tf aand Tf b) in Amazon Turtle (Podocnemis expansa Schweigger, 1812) - AS, Teixeira; AS, Moura; PHG, Oliveira; GN, Klein; NS, Tancredi; CA, Silva (Journal of Research in Biology, 2011)
This study aims to evaluate the temporal distribution of allele frequencies at the codominant transferrin (Tf ) gene locus in three population samples of Amazon turtle (Podocnemis expansa) collected from the Rio Uatumã, Rio Trombetas and Rio Tapajós in the Amazon Basin, Brazil, over a period of 16 to 24 years ago. Confirming previous research, the Tf locus which was analyzed by starch gel electrophoresis showed a diallelic polymorphism with the presence of theoretically expected genotypes (Tfaa, Tfab and Tfbb), presumably encoded by the codominant alleles (Tfa and Tfb). A good genetic fit according to Hardy-Weinberg expectations within and among all the population samples was also noticed. Contingency tests on the overall transferrin allele distributions by calculating the chi-square (x2) showed no statistically significant temporal variation (x2 = 3.05, d.f. = 5, 0.70 > P > 0.50) in the population samples of P. expansa in the surveyed areas